PENGARUH USABILITY, CUSTOMER SATISFACTION, CUSTOMER SERVICE DAN TRUST TERHADAP LOYALTY PENGGUNA MOBILE BANKING DI SURABAYA - Victoria Detra Johannes; Indarini Indarini; Silvia Margaretha (CALYPTRA, 2018)
The purpose of this research is to analyze the effect of Usability, Customer Satisfaction, Customer Service and Trust towards Loyalty of Mobile Banking user in Surabaya. The data that used in this researach are primary data that obtained from questionnaires. Respondent in this study are 200 respondents who live in Surabaya that are using mobile banking facility from BCA, BNI or Bank Mandiri for the past 6 months. Data processing was conducted using SPSS 18 for Windows and Amos Graphic 21 for Windows. The sampling technique that used is non-probability sampling with purposive sampling type.The result of this research shows that there is a positive effect between usability, customer satisfaction, customer service and trust towards loyalty.